1980
DOI: 10.1007/bf01068115
|View full text |Cite
|
Sign up to set email alerts
|

Implications for phonetic symbolism: The relationship between pure tones and geometric figures

Abstract: In studies of phonetic symbolism, the most commonly cited attribute of speech relevant to the phenomenon has been frequency. The present study was conducted in order to examine the relationship between pure tone frequencies and geometric figures. A pure tone oscillator was constructed which produced tones in a continuous sweep from 4-12,250 Hz. Six geometric shapes were employed and varied along three binary dimensions (size, complexity, and density) producing a total of 48 stimulus figures. Twelve male and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 9 publications
5
31
1
Order By: Relevance
“…One such non-speech experiment on sound symbolism was conducted by O'Boyle and Tarte (1980), who did not find a significant correlation between frequencies of pure tones and the figures that they represent. They moreover cite (apparently unpublished) results (Tarte 1976) which found that speakers associated low tones with small figures significantly more often than with large objects-a correlation opposite of the one that the frequency code hypothesis predicts.…”
Section: Summary: Articulatory or Acoustic?mentioning
confidence: 99%
See 1 more Smart Citation
“…One such non-speech experiment on sound symbolism was conducted by O'Boyle and Tarte (1980), who did not find a significant correlation between frequencies of pure tones and the figures that they represent. They moreover cite (apparently unpublished) results (Tarte 1976) which found that speakers associated low tones with small figures significantly more often than with large objects-a correlation opposite of the one that the frequency code hypothesis predicts.…”
Section: Summary: Articulatory or Acoustic?mentioning
confidence: 99%
“…tions based on the frequency code hypothesis (Ohala 1983b(Ohala , 1994see also Newman 1933;O'Boyle and Tarte 1980). This hypothesis builds on the correlation between the size of a resonator (or a resonating cavity) and its resulting frequency: lower frequencies imply large resonance cavities or resonators because the resonance frequency inversely correlates with its size.…”
mentioning
confidence: 99%
“…The majority of studies in the area of sound symbolism have tended to restrict themselves to detailing the existence of particular crossmodal associations (e.g., Boyle & Tarte, 1980;Holland & Wertheimer, 1964;Lindauer, 1990;Taylor, 1963), checking for the universality of such associations across cultures/languages (e.g., Davis, 1961;Gebels, 1969;Osgood, 1960;Rogers & Ross, 1975;Taylor & Taylor, 1962;see Hinton et al, 1994, for a review), and/or charting their emergence over the course of human development (e.g., Irwin & Newland, 1940;Maurer, Pathman, & Mondloch, 2006). Interestingly, the latest research suggests that neuropsychological factors may also impact on the expression of crossmodal correspondences: It has, for instance, been reported that children with autism spectrum disorder do not show the bouba/kiki effect (Oberman & Ramachandran, 2008;Ramachandran & Oberman, 2006).…”
Section: Crossmodal Correspondences: Early Research On Crossmodal Matmentioning
confidence: 99%
“…Note that angularity, bitterness, and carbonation are all initially disliked as stimuli [55,56]. The common meanings associated with different kinds of sensory stimuli [57][58][59][60] may therefore provide a possible explanation for at least certain of the shape symbolism effects that have been documented in the food and beverage sector to date. The affective value, or pleasantness, of sensory stimuli therefore provides one way in which the 'meaning' of very different types of sensory stimuli could be matched.…”
Section: Using Shape Symbolism To Set Consumer Expectations In the Fomentioning
confidence: 99%